Electrocatalysis on Noble Metal and Noble Metal Alloys Dispersed on High Surface Area Carbon - Pinheiro, Alexei L.N. (2003)
In this work, a simple route to prepare carbon supported Pt/C, Pt:Ru/C, Pt:Mo/C, and Pt:Ru:Mo/C catalysts is reported. The electrochemical properties of the several carbon materials used as substrates in the absence and in the presence of supported platinum and platinum alloys catalysts were investigated using cyclic voltammetry and employing the thin porous coating electrode technique. The activity of the dispersed catalysts composed of Pt/C with respect to the oxygen reduction and of alloy/C with respect to methanol oxidation was investigated using steady state polarization measurements. The performance with respect to the oxygen reduction reaction of the Pt/C catalyst prepared on heat-treated Vulcan carbon substrate is equivalent to that reported in the literature for the state-of-the-art electrocatysts. Pt:Ru:Mo/C samples prepared in this work presented the higher catalytic effect for methanol electro-oxidation.